Elevating Critical Thinking: English Online Peer Discussion on Padlet - Sari, Angela Bayu Pertama; Iswahyuni, Dwi; Rejeki, Sri; Yogyanti, Devita Widyaningtyas (PROJECT (Professional Journal of English Education), 2025)
This qualitative study investigates the development of students' critical thinking skills through online English discussion learning activities on the Padlet platform. This study involved 130 respondents from non-English majors. The researchers collected data using an open questionnaire, which was then analyzed based on thematic data analysis. The study's results showed several factors that significantly impacted the improvement of students' critical thinking quality: interesting discussion topics that stimulate active discussion, time limits that encourage focused delivery of ideas, and vocabulary exposure that improves students' ability and fluency in expressing their opinions in English. More deeply, peer opinions in the discussion process are important in sharpening students' critical thinking skills. Various student perspectives enrich knowledge and deepen students' understanding of a discussion topic. The study results showed that several students who initially did not understand the discussion topic were enlightened and inspired to express their opinions after reading their peers' arguments. The language exposure presented in the discussion also strengthened students' ability to express their critical thinking. Overall, discussions through the Padlet platform created a conducive, comfortable and effective atmosphere supporting online English learning.